A phenomenological explication of the experience of having one's bereavement denied by others - Sennett, Margot Jane (Rhodes University, Faculty of Humanities, Department of Psychology, 1988)
Bereavement is the natural human reaction to the death of a significant other. Often the experience of the bereaved person is denied expression in the social context. The aim of this thesis is to examine what it means to have one's bereavement denied by others. The relevant literature was reviewed. Theories which have both reflected and influenced the way the bereaved are perceived in contemporary western society have been discussed. The historical background to changing attitudes towards death was described and the reasons for the "denial of death" were examined . The narcissistic personality in particular was considered . Using the Phenomenological method, a question was formulated to elicit the lived structure of the experience being researched. This was asked of thirteen voluntary subjects who had experienced the denial of their bereavement by others. Five written answers (protocols) were chosen and explicated. The lived structure of the experience can be described as "a profound and fundamental distancing of the world of the bereaved from the world of others." The implications of this for the bereaved person, bereavement support groups, health care professionals, future research and society as a whole were then critically discussed .
Keywords: Death -- Psychological aspects; Bereavement; Grief